(untitled) (Baghdad Science Journal, 2004)
The aim of this research is to study the effect of welded joint design (Butt joint and lap joint) on thejoint strength during tension and fatigue loading with different current of welding (40,50,60,70,80) ^per, and different type of wire welding. The result of this research is showed that the effect of fatigue loading on the type of joint is more than the effect of tension loading on it. And the butt joint welding is better than the lap joint welding during the fatigue loaded.The experimental results of the effect of W’elding current showed that more increasing and more decreasing the value of the heat input, during the welding was found to produce mechanical brittleness on the buttjoint welding during the static and dynamic loading. Also it was found that welded lap joint properties are improved when the welding current is increase during the static and dynamic loading. Results indicate too that the more effect of the type of wires welding on the welded joint during the static and dynamic loading.?